2019
DOI: 10.1186/s13638-019-1378-4
|View full text |Cite
|
Sign up to set email alerts
|

SWIPT in mMIMO system with non-linear energy-harvesting terminals: protocol design and performance optimization

Abstract: In this paper, we design the simultaneous wireless information and power transfer (SWIPT) protocol for massive multi-input multi-output (mMIMO) system with non-linear energy-harvesting (EH) terminals. In this system, the base station (BS) serves a set of uplink fixed half-duplex (HD) terminals with non-linear energy harvester. Considering the non-linearity of practical energy-harvesting circuits, we adopt the realistic non-linear EH model rather than the idealistic linear EH model. The proposed SWIPT protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…By considering best relay selection beamforming criterion giving best performance in terms of OP considering relay, source and destination, analytical expression of OP was calculated and validated through simulations. In [130], authors developed a SWIPT based protocol by considering non-linear energy harvesting model in massive MIMO systems. Here a more realistic power consumption scheme was suggested.…”
Section: E Mimo With Nonlinear Eh and Imperfect Csimentioning
confidence: 99%
“…By considering best relay selection beamforming criterion giving best performance in terms of OP considering relay, source and destination, analytical expression of OP was calculated and validated through simulations. In [130], authors developed a SWIPT based protocol by considering non-linear energy harvesting model in massive MIMO systems. Here a more realistic power consumption scheme was suggested.…”
Section: E Mimo With Nonlinear Eh and Imperfect Csimentioning
confidence: 99%
“…An optimization problem and solution is developed in [12] to maximize the sum throughput of a wireless powered communication network. A non-linear Energy extraction model is well suitable for MIMO networks rather than the idealistic linear EH model [13]. Authors in [14] focused on imposing energy constraints while the current energy always is ensured to be greater than a predefined threshold.…”
Section: A Related Workmentioning
confidence: 99%
“…In the above schedule, W k is determined by B k−1 with known values of E k . It is assumed that B 0 = 0, W k can be obtained by computing (17), (16) and (13) for k = 1, 2, . .…”
Section: Energy Optimization Using Greedy Policymentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, there have been many works investigating the benefits of both EH and FD techniques in WIPT-FDR systems through mathematical analyses or simulations. Although linear energy harvester has been widely used in the literature, recent reports such as [26]- [29] demonstrated that it might be impractical. In fact, there are various factors causing the nonlinear characteristic of energy harvester such as diode and saturation nonlinearities.…”
Section: Introductionmentioning
confidence: 99%